2015
DOI: 10.1002/anie.201502358
|View full text |Cite
|
Sign up to set email alerts
|

Ring Tension Applied to Thiol‐Mediated Cellular Uptake

Abstract: The objective of the study was to explore the potential of ring tension in cyclic disulfides for thiol-mediated cellular uptake. Fluorescent probes that cannot enter cells were equipped with cyclic disulfides of gradually increasing ring tension. As demonstrated by flow cytometry experiments, uptake into HeLa Kyoto cells increased with increasing tension. Differences in carbon-sulfur-sulfur-carbon (CSSC) dihedral angles as small as 8° caused significant changes in uptake efficiency. Uptake with high ring tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
177
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(184 citation statements)
references
References 42 publications
5
177
2
Order By: Relevance
“…Contrary to AspA controls, 12,13 the removal of thiols on cell surfaces with maleimide 26 , 22 iodoacetamide 27 , 12 and the most powerful hypervalent iodine reagent 28 (29) failed to inactivate ETP 6 (Figure 4C). Similarly, the presence of 10% serum 22 caused only a minor ∼25% reduction of ETP uptake (Figures 4C and S5).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Contrary to AspA controls, 12,13 the removal of thiols on cell surfaces with maleimide 26 , 22 iodoacetamide 27 , 12 and the most powerful hypervalent iodine reagent 28 (29) failed to inactivate ETP 6 (Figure 4C). Similarly, the presence of 10% serum 22 caused only a minor ∼25% reduction of ETP uptake (Figures 4C and S5).…”
Section: Resultsmentioning
confidence: 93%
“…11 Uptake efficiencies were found to increase with ring tension from relaxed disulfides 3 with θ ≈ 90° to lipoic acid derivatives 4 with θ = 35° and asparagusic acid derivatives 5 with θ = 27°. 12,13 The most efficient “AspA tag” as in 5 allowed the delivery of functional peptides, 14 liposomes and polymersomes 13 into cells, and the transferrin receptor (TFRC) has been identified as one of the targets. 14 The power and promise of strain-promoted thiol-mediated uptake at θ = 27° provided a compelling incentive to drive disulfide ring tension to the extreme.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been shown that lipoic acid-based vesicles show remarkable polymerization/depolymerization properties, thereby offering a possible route to both effi ciently protect and release encapsulated entities. [50][51][52] Furthermore, their biological potential has been recently realized as unique motifs to trigger cellular uptake per se, so-called cell-penetrating poly(disulfi de)s, [53][54][55] which show noteworthy delivery profi les; [56] thus underlining the outstanding suitability of lipoic acid entities for drug and gene delivery applications. [57][58][59][60] All building blocks were selected in that they represent nontoxic entities in order to preferably generate biocompatible gene carriers that additionally, after successful nucleic acid delivery, do not raise toxic effects following intracellular fragmentation.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…[5] Benzopolysulfane rings are not very strained (XSSX dihedral angles ! [1][2][3][4][5][6][7] This extreme sulfur chemistry attracted our attention in our search for new ways to enter cells.F rom cell-penetrating peptides (CPPs) [8] to cell-penetrating poly(disulfide)s (CPDs) [9] and COCs, [10][11][12][13] the cellular uptake via dynamic covalent dichalcogenide exchange chemistry has come to prominence,o ften referred to as thiol-mediated uptake,w ith exofacial thiols as initial targets and continuing on the way into the cell. [1][2][3][4][5][6][7] This extreme sulfur chemistry attracted our attention in our search for new ways to enter cells.F rom cell-penetrating peptides (CPPs) [8] to cell-penetrating poly(disulfide)s (CPDs) [9] and COCs, [10][11][12][13] the cellular uptake via dynamic covalent dichalcogenide exchange chemistry has come to prominence,o ften referred to as thiol-mediated uptake,w ith exofacial thiols as initial targets and continuing on the way into the cell.…”
mentioning
confidence: 99%
“…728 8), [6] but excel with unique,complex chemistry. [10][11][12][13][14][15] Promising results with strained cyclic disulfides [10,11] and diselenides [12,13] called for as hift of attention to the extreme sulfur chemistry of higher oligochalcogenides. [10][11][12][13][14][15] Promising results with strained cyclic disulfides [10,11] and diselenides [12,13] called for as hift of attention to the extreme sulfur chemistry of higher oligochalcogenides.…”
mentioning
confidence: 99%